2017
DOI: 10.15294/jbat.v6i1.7168
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Breadfruit Flour: Effect of Heater Temperature to the Drying Rate and Time of the Breadfruit

Abstract: The composition of mineral and vitamin from breadfruit is particularly known of having benefits compared to rice which is a main source of carbohydrate consumed by societies. The process of drying is one of the factors that affects foodstuffs quality. The aim of this research was to provide an understanding of drying phenomena from data experiment and discover the influence of drying air temperature to breadfruit drying time and rates. This research was conducted in several stages which are material preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…This can be manually mashed into a paste to make a sweet snack or cooked in curries ( 20 ). This drying process is necessary to halt the fermentation process and the growth of bacteria and fungi ( 21 ). Another method of extending the shelf life of breadfruit involves pit storage fermentation.…”
Section: Breadfruit Pulp Processingmentioning
confidence: 99%
See 3 more Smart Citations
“…This can be manually mashed into a paste to make a sweet snack or cooked in curries ( 20 ). This drying process is necessary to halt the fermentation process and the growth of bacteria and fungi ( 21 ). Another method of extending the shelf life of breadfruit involves pit storage fermentation.…”
Section: Breadfruit Pulp Processingmentioning
confidence: 99%
“…A better retention of nutritional qualities of breadfruit flour (using matured fruit) was noticed when the oven drying method was used ( 19 ). Sari and Lestari found that the optimum breadfruit flour production in terms of appearance was achieved with a temperature of 60 ° C and a drying time of 100 min ( 21 ). At 60 ° C, minimal browning of the flour via Maillard reaction occurs and as temperature rises, more Maillard reaction was seen.…”
Section: Breadfruit Pulp Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Breadfruit can be used as an alternative food source for the local community. It contains carbohydrates used as organic carbon sources for the local community (Sari & Lestari, 2017). Besides, the green culinary concept also needs to use green cutlery that does not cause any environmental problems in the peat ecosystem.…”
Section: Zone II (Utilization)mentioning
confidence: 99%